Cooperative Management of a Traditional Irrigation System in the Swiss Alps - Robert Finger; Anna Borer (Social Sciences, 2013)
Traditional channel irrigation systems in Switzerland are managed on a community basis and have high cultural, touristic and ecological values. However, many irrigation communities disappeared in the last decades. This paper analyzes the factors contributing to the continuation of a still existent irrigation community. Our analysis thus provides insights into how to avoid further losses of these unique agricultural systems and to preserve the associated benefits. Based on hypotheses derived from game theoretical analysis, a survey was conducted in an irrigation community located in the canton of Valais. Our results show that the motivation of community members to remain in the traditional system is not a financial one. In contrast, factors such as long-term perspectives, system knowledge, communication and the institutional setting seem to be the basis for the continuation of the analyzed irrigation community. For policy makers, this example shows that the creation of institutions that enable self-governance, communication and knowledge transfer should be considered in this field of rural and agricultural policy making.